Psychometric properties of the emotional dependence questionnaire (CDE) in university students - Vargas Pérez, Norma Haydeé (2020)
The present research work aimed to determine the psychometric properties of the Emotional Dependence Questionnaire (CDE) adapted in Peru by Guerra and Mego (2011), based on the one originally prepared by Lemos and Londoño (2006). The population consisted of 700 first-cycle students from 3 Chiclayo universities, whose ages ranged from 16 to 25 years old. The data analysis was carried out through the SPSS program, at first the content validity was obtained through the criterion of expert judgment, obtaining values from 0.60 to 1 in the three evaluated indicators (Clarity, coherence and relevance). For reliability, the internal consistency method was used through Cronbach's alpha statistic, having a general value of 0.94, indicating that the questionnaire is valid and reliable. Finally, the scales were updated through percentiles, for the qualification of the instrument in the population studied.